A systematic review on the relationship between self-esteem and interrogative suggestibility - Hooper, Victoria-Rose; Chou, Shihning; Browne, Kevin D. (Taylor & Francis, 2016)
Some factors, such as age, learning disability and mental health difficulties, have been identified as making police suspects more vulnerable to suggestibility and false confessions during interview. However, there has been no systematic review on the association between self-esteem and suggestibility.